Being Flexible: The Voltage-Controllable Activation Gate of Kv Channels - Labro, Alain J.; Snyders, Dirk J. (Frontiers in Pharmacology, 2012)
Kv channels form voltage-dependent potassium selective pores in the outer cell membrane and are composed out of four -subunits, each having six membrane-spanning -helices (S1-S6). The -subunits tetramerize such that the S5-S6 pore domains co-assemble into a centrally located K+ pore which is surrounded by four operational voltage sensing domains (VSD) that are each formed by the S1-S4 segments. Consequently, each subunit is capable of responding to changes in membrane potential and dictates whether the pore should be conductive or not. K+ permeation through the pore can be sealed off by two separate gates in series: (a) at the inner S6 bundle crossing (BC gate) and (b) at the level of the selectivity-filter (SF gate) located at the extracellular entrance of the pore. Within the last years a general consensus emerged that a direct communication between the S4S5-linker and the bottom part of S6 (S6c) constitutes the coupling with the VSD thus making the BC gate the main voltage-controllable activation gate. While the BC gate listens to the VSD, the SF changes its conformation depending on the status of the BC gate. Through the eyes of an entering K+ ion, the operation of the BC gate apparatus can be compared with the iris-like motion of the diaphragm from a camera whereby its diameter widens. Two main gating motions have been proposed to create this BC gate widening: (1) tilting of the helix whereby the S6 converts from a straight -helix to a tilted one or (2) swiveling of the S6c whereby the S6 remains bent. Such motions require a flexible hinge that decouples the pre- and post-hinge segment. Roughly at the middle of the S6 there exists a highly conserved glycine residue and a tandem proline motif that seem to fulfill the role of a gating hinge which allows for tilting/swiveling/rotations of the post-hinge S6 segment. In this review we delineate our current view on the operation of the BC gate for controlling K+ permeation in Kv channels.